2020
DOI: 10.1177/0963689720954798
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility of Cryopreserved Insulin-producing Cells Differentiated from Adipose-tissue-derived Stem Cells

Abstract: The aim of our study is to determine whether insulin-producing cells (IPCs) differentiated from adipose-tissue-derived stem cells (ADSCs) can be cryopreserved. Human ADSCs were differentiated into IPCs using our two-step protocol encompassing a three-dimensional culture and xenoantigen-free method. Thereafter, IPCs were frozen using three different methods. First, IPCs were immediately frozen at −80°C (−80°C group). Second, IPCs were initially placed into a Bicell freezing container before freezing at −80°C (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…However, this study still has some shortcomings as theses SLCs (FA) generated by our modified protocol are still in conventional two-dimensional pattern. Many researchers including our team (8,9,11,43) have illustrated that the three-dimensional (3D) cell culture pattern could promote the differentiation efficiency of stem cells and improve the final therapeutic effect of cell transplantation and cell therapy, which is considered to be the trend of tissue engineering and regeneration medicine. Therefore, we decide and have already begun to apply this new protocol combined with 3D culture technology for the generation of more powerful SLCs and explore its potential on the nerve regeneration in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study still has some shortcomings as theses SLCs (FA) generated by our modified protocol are still in conventional two-dimensional pattern. Many researchers including our team (8,9,11,43) have illustrated that the three-dimensional (3D) cell culture pattern could promote the differentiation efficiency of stem cells and improve the final therapeutic effect of cell transplantation and cell therapy, which is considered to be the trend of tissue engineering and regeneration medicine. Therefore, we decide and have already begun to apply this new protocol combined with 3D culture technology for the generation of more powerful SLCs and explore its potential on the nerve regeneration in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose-derived stem cells (ADSCs) have been focused on because of their multipotency and ease of harvest. We have investigated ADSC multipotency and reported scientific evidence of insulin producing cells (IPCs) for clinical applications (7)(8)(9)(10)(11). Thus, we hypothesized that ADSCs can also self-renew and differentiate into ectodermal lineage cells, including Schwann-like cells (SLCs).…”
Section: Introductionmentioning
confidence: 99%
“…We used immunofluorescence procedures in our department that were previously reported [52]. Anti-OPN antibody (dilution 1:1000, ab8448; Abcam plc.…”
Section: Immunofluorescencementioning
confidence: 99%
“…We have previously reported the generation of functional IPCs from ADSCs 5 with three-dimensional (3D) culture and a xenoantigen-free protocol 6 10 . The quality and functionality of IPCs generated in this way have been assessed using techniques such as the stimulation index (SI), which can be used to evaluate autonomous glucose response ability, and showed that the cells have satisfactory functionality for clinical use 5 10 .…”
Section: Introductionmentioning
confidence: 99%